Prospek dan Strategi Pengembangan Pala di Maluku - SJAHRUL BUSTAMAN (Puslitbang Perkebunan, 2007)
ABSTRAKPala Banda (Myristica fragrans Houtt) adalah komoditas utama pada program revitalisasi perkebunan Provinsi Maluku dan merupakan tanaman asli daerah. Di tahun 2005 produksi pala rakyat 1998 ton pada luas lahan 1948 Ha, sedangkan perusahaan perkebunan menghasilkan 2357 ton dari luas areal 10.128 Ha, dengan harga biji pada kualitas terbaik Rp 30.000/kg dan fuli Rp 50.000/kg. Dari hasil kajian Agro Ekologi Zona (AEZ) Maluku, luas lahan yang masih tersedia untuk pengembangan tanaman perkebunan termasuk pala sebesar 871.656 Ha yang tersebar pada lima kabupaten. Tanaman pala yang ada saat ini bibitnya berasal dari biji sehingga masalah sex ratio untuk menghasilkan buah masih ditemukan. Komposisi tanaman pala rakyat terdiri dari (1) Tanaman Belum Menghasilkan (TBM) sebanyak 27,85%; (2) Tanaman Menghasilkan (TM) 44,74% dan Tanaman Tua/Rusak (TTR)27,40%. Dalam usaha pengembangan pala, ketersediaan teknologi budidaya tanaman dan pasca panen telah ada di Badan Litbang Pertanian, sedangkan dukungan dana dan kebijakan diharapkan dari pemerintah daerah guna memulihkan kondisi tanaman. Di sektor hulu, kebijakan lebih diarahkan kepada peningkatan produktivitas, mutu biji dan fuli pala melalui kegiatan ekstensifikasi, intensifikasi, rehabilitasi, peremajaan, serta pengendalian hama dan penyakit pala. Sedangkan di sektor hilir, kebijakan lebih diarahkan kepada peningkatan nilai tambah dalam bentuk hasil olahan untuk industri dan panganan. Propinsi Maluku terdiri dari wilayah kepulauan, sehingga strategi pengembangan usaha pala untuk kegiatan agribisnis dibagi atas wilayah pengembangan I, II dan III.Kata kunci: Pala, Myristica fragrant, pengembangan, Maluku. ABSTRACTProspect and Development Strategy of Nutmeg Development In MalukuBanda’s Nutmeg (Myristica fragrant Houtt) is the main commodity of the estate crop revitalization program in Maluku Province, which is native to the region. In year 2005 the total area of the small holder nutmeg crop is about 1948 ha with the total production of about 1998 tons. While the total estate nutmeg crop covers about 10.128 ha with the total production of about 2357 tons. The price of nutmeg seed is about Rp 30.000 / kg and the price of fuli is Rp.50.000 /kg. According to the survey carried out by the BPTP Maluku, the total land which is still available for the development of estate crop including nutmeg is around 871.656 ha, spread over five Regencies (Kabupaten). The existing nutmeg plants is generally come from seedlings, therefore the sex ratio in producing nutmeg fruits is still a major constraint. The composition of small holder nutmeg plantation consists of; (i) Not yet producing (young plants) counts about 27,85% (ii) Productive plants of about 44,74% and (iii) Old plants of about 27,40%. Both cultivation and post harvest technology for nutmeg plantation are available in the Agency for Agriculture Research and Development (Badan Litbang Pertanian). The regional authority should be convinced the necessity of supporting plant rehabilitation in order to produce good quality nutmeg and in turn as the regional income source. In the cultivation sector, the policy is to increase productivity of fruit and fuli quality which is implemented through rehabilitation, intensification, replantation, pests and disease control. In the upstream sector, the policy is directed to improve the added value of post harvest in terms of products for industrial materials and food production. The province of Maluku consists of several islands, therefore the strategy of the nutmeg agribusiness development is divided into regional development I, II and III.Key words: Nutmeg, Myristica fragrans, development, Maluku